2018
DOI: 10.1097/opx.0000000000001227
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Cheating when Testing Vision: Variability in Acuity Measures Reveals Misrepresentation

Abstract: The variability in the estimations of vision provides a promising novel means of detecting the intentional underrepresentation of vision and could help to minimize the chance of successfully cheating on tests of vision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…The highest priority of our panel was to introduce less subjective testing, because current methods rely on athletes to provide their best effort and honest answers. One approach to increase objectivity in classification is to take into account the consistency of test performance, which may hold promise as an indicator whether or not the athlete provided their best effort and honest answers (Deuble et al, 2016; Ravensbergen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The highest priority of our panel was to introduce less subjective testing, because current methods rely on athletes to provide their best effort and honest answers. One approach to increase objectivity in classification is to take into account the consistency of test performance, which may hold promise as an indicator whether or not the athlete provided their best effort and honest answers (Deuble et al, 2016; Ravensbergen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Another potential limitation of the study is that the measurement of visual acuity and contrast sensitivity relies on the subjective and therefore honest responses of participants. These subjective tests are susceptible to intentional misrepresentation, where a potential athlete may willfully perform poorly to appear as though their vision is worse than it actually is (Ravensbergen et al, 2018; Krabben et al, 2019). A more objective method of measuring visual acuity and contrast sensitivity is desirable because it would reduce the risk of intentional misrepresentation.…”
Section: Discussionmentioning
confidence: 99%
“…On-site evaluation with electrophysiology experts who can properly assess visual potential with pattern visual evoked potentials and eletroretinograms 22,56 in addition to recently improved methods for visual acuity assessment 55,57 has improved classification methods for detecting and preventing athlete misrepresentation. For example, Ravensbergen et al 55 have demonstrated how high variability in visual acuity estimations using the tumbling E optotypes of Berkeley Rudimentary Vision Test can be one way to detect intentional misrepresentation. 57 More of these carefully designed investigations that refine the psychophysical methods of accurately determining repeatable visual acuity and visual field estimations for sports classification will indeed minimize opportunities for athletes to malinger.…”
Section: Classification Challengesmentioning
confidence: 99%
“…The rapid growth of the Paralympic movement has raised the stakes for Paralympians who have a chance at international recognition in addition to monetary awards. Unfortunately, on the rare occasion, athletes may be tempted to cheat or engage in “intentional misrepresentation.” 11,55 This is when athletes feign their diagnosis or severity of their vision impairment to compete in a sport or sport class. Diagnoses like amblyopia, high myopia, and even those that are associated with disorders of the visual pathway can become challenging to distinguish from athlete misrepresentation because we are limited to mainly relying on electrophysiology testing to confirm an eligible impairment.…”
Section: Classification Challengesmentioning
confidence: 99%